2016
DOI: 10.1136/bmjopen-2016-011634
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Imagination: a mixed-methods protocol for arts and science research

Abstract: IntroductionDementia and Imagination is a multidisciplinary research collaboration bringing together arts and science to address current evidence limitations around the benefits of visual art activities in dementia care. The research questions ask: Can art improve quality of life and well-being? If it does make a difference, how does it do this—and why? Does it have wider social and community benefits?Methods and analysisThis mixed-methods study recruits participants from residential care homes, National Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…To our knowledge, this is the first study of its kind to investigate the salivary diurnal cortisol rhythm in response to a psychosocial intervention for PLWD, and we determined this sample size to be suitable to provide useful data to inform future studies. A similar pragmatic approach has been used in a large Art and Dementia study in the United Kingdom [30]. All variables were examined prior to analysis to determine suitability for parametric or non-parametric methods using histograms and both Kolmogorov-Smirnov and Shapiro-Wilk tests of normality.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first study of its kind to investigate the salivary diurnal cortisol rhythm in response to a psychosocial intervention for PLWD, and we determined this sample size to be suitable to provide useful data to inform future studies. A similar pragmatic approach has been used in a large Art and Dementia study in the United Kingdom [30]. All variables were examined prior to analysis to determine suitability for parametric or non-parametric methods using histograms and both Kolmogorov-Smirnov and Shapiro-Wilk tests of normality.…”
Section: Methodsmentioning
confidence: 99%
“…A recruitment protocol was developed which emphasised that participants could pull out of the project at any time without explanation. The provisions of the UK Mental Capacity Act 2005 were followed and if the potential participant was unable to make an informed choice, an authorised family member or carer provided consent on their behalf, as is noted in the research protocol (Windle et al 2016). Research staff and artists undertook training by the lead investigators and this covered the Mental Capacity Act 2005, informed consent, dementia awareness and the study protocol procedures, including data collection methods and data management.…”
Section: Methodology Data and Visual Arts Enrichment Activitymentioning
confidence: 99%
“…The assessment of the studies methodological strengths and weaknesses during this review found that all the studies produced valuable results in terms of their contribution to knowledge and regarding the aims of this review. However, only Clarke et al (27,28) and Newman et al (29,30) rated highly in terms of methodological quality. This result was obtained by the two reviewers whose independent assessments, which initially revealed a high degree of consensus, achieved full consensus following discussion (Appendix ii in Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in 53 studies being retained for full-text review, against the inclusion criteria. The final review included six papers that reported five interventions (27)(28)(29)(30)(31)(32). An overview of the studies and the interventions is provided below.…”
Section: Review Findingsmentioning
confidence: 99%